2004
DOI: 10.1007/978-3-540-24605-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Satisfiability and Computing van der Waerden Numbers

Abstract: Abstract. In this paper we bring together the areas of combinatorics and propositional satisfiability. Many combinatorial theorems establish, often constructively, the existence of positive integer functions, without actually providing their closed algebraic form or tight lower and upper bounds. The area of Ramsey theory is especially rich in such results. Using the problem of computing van der Waerden numbers as an example, we show that these problems can be represented by parameterized propositional theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The proof is essentially the same as the proof given by Graham [7] of an upper bound for w 1 (k, 3). For completeness, we include the proof here.…”
Section: Upper and Lower Bounds For Certain Van Der Waerden Functionsmentioning
confidence: 91%
See 1 more Smart Citation
“…The proof is essentially the same as the proof given by Graham [7] of an upper bound for w 1 (k, 3). For completeness, we include the proof here.…”
Section: Upper and Lower Bounds For Certain Van Der Waerden Functionsmentioning
confidence: 91%
“…A list of other known exact values of w(k, m; 2) appears in [15]. Improved lower bounds on several specific values of w(k, k; s) are given in [3] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…For both these numbers, the encoding in [1,8] takes more than a couple of months to prove the corresponding instances unsatisfiable.…”
Section: An Observationmentioning
confidence: 99%
“…In [4], we showed that WSAT (CC ) is often much faster than a local-search SAT solver WSAT and has, in general, a higher success rate (likelihood that it will find a model if an input theory has one). In [1], we used WSAT (CC ) to compute several new lower bounds for van der Waerden numbers. Here, we will discuss our recent comparisons of WSAT (CC ) with WSAT (OIP ) [7], a solver for propositional theories extended with pseudo-boolean constraints (for which we developed utilities allowing it to accept PL cc theories).…”
Section: Performancementioning
confidence: 99%